Not JK Clark Said:
>A = B
>
>Multiply both sides by A and you have
>
>A^2 = A*B
>
>Now add A^2 -2*a*B to both sides
>
NOTE that A^2 - 2*A*b = - A*B
>A^2 + A^2 -2*a*B = A*B + A^2 -2*A*B
>
Resulting in 0 = 0
>Using basic algebra this can be simplified to
>
>2*( A^2 -A*B) = A^2 -A*B
>
So, 2 * 0 = 0
>Now just divide both sides by A^2 -A*B (which evaluates to 0)
Here is the illegal operation, division by Zero is UNDEFINED,
and we get
>
>2 = 1
Ian will love this!
O--------------------------------O | Hara Ra <harara@shamanics.com> | | Box 8334 Santa Cruz, CA 95061 | | | | Death is for animals; | | immortality for gods. | | Technology is the means by |
O--------------------------------O